2013
DOI: 10.3109/02713683.2013.841255
|View full text |Cite
|
Sign up to set email alerts
|

Human Corneal Epithelial Cell Shedding and Fluorescein Staining in Response to Silicone Hydrogel Lenses and Contact Lens Disinfecting Solutions

Abstract: This pilot study indicates that increased epithelial cell shedding was associated with a lens-solution combination which induces SICS. Our data provides insight into the transient nature of the SICS reaction and the nature of fluorescein staining observed in SICS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This suggested that the increased staining was unrelated to increased shedding due to impaired epithelial health. However, Gorbet et al (2014), using the same technique, reported increased epithelial cell shedding during acute exposure to MPS release from an SiHy lens.…”
Section: Discussionmentioning
confidence: 87%
“…This suggested that the increased staining was unrelated to increased shedding due to impaired epithelial health. However, Gorbet et al (2014), using the same technique, reported increased epithelial cell shedding during acute exposure to MPS release from an SiHy lens.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the tear turnover rate has been published to fall with less concentrated fluorescein attributable to a contribution from persistent corneal fluorescence (King-Smith et al, 2013). In fluorophotometry experiments (de Kruijf et al, 1987; McNamara et al, 1997), fluorescence persists for 15–20 min despite tear washout (Gorbet et al, 2014; Joshi et al, 1996). The degree to which the fluorescence emanates from the epithelium as opposed to the stroma is not established.…”
Section: Resultsmentioning
confidence: 99%
“…However, some details are inconsistent with this hypothesis. Caspase positive cells do not admit fluorescein (Gorbet et al, 2014) and many hyperfluorescent cells do not show apoptosis (Mokhtarzadeh et al, 2011). Therefore, an active transport exchange of monocarboxylate species that includes fluorescein has been proposed in stressed cells (Yeh et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] By studying the occurrence of solution-related staining, some authors focused the attention on different combinations of (1) type of lens and (2) maintenance solution and found clear evidence of combined clinical effects. 6,7,9,10 The advent of silicone hydrogel (SH) CLs raised even more the attention on ocular surface reactions because of the physical and chemical characteristics of the materials. 5-8,10-13 Papas et al 8 pointed out that lens care products developed for conventional hydrogel CLs may not be entirely compatible with SH CLs.…”
mentioning
confidence: 99%